Pengaruh Pengetahuan Anggota dan Kreativitas Pengurus terhadap Partisipasi Anggota Koperasi Karyawan PT Indoneptune Rancaekek - Wazdi, Adi Indradi; Firman, Yosep (Universitas Ma'soem, 2021)
Based on the results of the observation that this research is based on, which is the variability of participation by the member of Koperasi Karyawan PT. Indoneptune Rancaekek. The research aims to determine how the effect/influence of member’s knowledge on member’s participation, to determine the impact of management’s creativity on member participation, also to verify the impact of the member’s knowledge and management’s creativity instantaneously on the member’s participation as a whole on the members of Koperasi Karyawan PT. Indoneptune Rancaekek. This is an associative quantitative type of research. The type where the data is a primer and uses a form of observation, interviews, literature study and questionnaires as its techniques to collect the data from. While using a random sampling technique out of 86 people from 591 members. The results shown that there are no significant effect/influence between the member’s knowledge and the member participation, with t test result where tcount < ttable (0,948 < 1,66342). Meanwhile there was significant result concerning the influence between the management’s creativity and the participation of the members, with tcount > ttable (-4.060> 1.66342). Simultaneously there was a significant spike of impact/influence between the member’s knowledge and the management’s creativity on the members participation of Koperasi Karyawan PT. Indoneptune Rancaekek using the F test where the Fcount > Ftable (8.151 > 2.37).